Effects of home bleaching agents on hybrid ceramics: mechanical properties and color change - Waleed M. Hafny; Imam M. Ibrahim; Mohamed El-Demellawy; Hoda M. Abdel Sadek (BMC Oral Health)
Abstract Background Home bleaching is a promising option for addressing discolored teeth conservatively. However, its impact on the physical and mechanical properties of indirect restorations remains unknown. This study provides comparative insights into the material responses to aesthetic treatments by assessing the effects of home bleaching agents on two hybrid ceramics: VITA ENAMIC® and Grandio Blocs. The focus is on evaluating color stability and biaxial flexural strength. Methods 60 discs (12 × 1 mm) were prepared from hybrid ceramics. Specimens were divided into two groups according to type of hybrid ceramic (30 specimens in each group); group A: VITA ENAMIC®, group B: Grandio Blocs. Each group was further subdivided into 3 subgroups according to the concentration of home bleaching agents used (10 specimens in each subgroup); subgroup C: unbleached control group, subgroup C10%: carbamide peroxide 10% bleaching agent, and subgroup C35%: carbamide peroxide 35% bleaching agent. Samples of subgroup C10% were bleached with Home Bleaching Opalescence PF (10%) for 8 h per day for 14 days, as directed by the manufacturer. Samples of subgroup C35% were bleached using WHITEsmile Carbamide Peroxide (35%), following the manufacturer’s directions for 30 min every day for 14 days. Color change (ΔE) was assessed using of the CIE L*a*b* system. Then, the biaxial flexural strength test was done. The data were analyzed using two-way ANOVA tests and Weibull analysis. Results VITA ENAMIC samples exhibited significantly higher color change than Grandio Blocs (p < 0.001), while Grandio Blocs showed significantly higher biaxial flexural strength (p < 0.001). The concentration of the bleaching agent had no significant effect on color change (p = 0.086). However, regardless of its concentration, bleaching significantly reduced biaxial flexural strength in both materials (p < 0.001). Weibull analysis showed that Grandio Blocs had higher characteristic strength, while VITA ENAMIC demonstrated more reliable failure behavior. Conclusions Compared to Grandio Blocs, VITA ENAMIC® exhibited a greater color change with both 10% and 35% carbamide peroxide home bleaching agents. Additionally, both concentrations of carbamide peroxide reduced the biaxial flexural strength of hybrid ceramics. These findings can guide clinicians in selecting hybrid ceramics based on clinical demands for aesthetics and durability. VITA ENAMIC® offers greater structural reliability and predictability for aesthetic restorations, while Grandio Blocs provide superior durability and stress resistance for high-stress clinical applications.